Pembrolizumab Versus Placebo as second-line therapy in patients From Asia with advanced hepatocellular carcinoma: A randomized, double-blind, phase III trial - Qin, Shukui (American Society of Clinical Oncology, 2023)
We evaluated the efficacy and safety of pembrolizumab in patients from Asia with previously treated advanced hepatocellular carcinoma (HCC).METHODSIn a double-blind, phase III trial, 453 patients with advanced HCC and progression during or after treatment with or intolerance to sorafenib or oxaliplatin-based chemotherapy were randomly assigned in a 2:1 ratio to receive pembrolizumab (200 mg) or placebo once every 3 weeks for <= 35 cycles plus best supportive care. The primary end point was overall survival (one-sided significance threshold, P = .0193 final analysis]). Secondary end points included progression-free survival (PFS) and objective response rate (ORR; one-sided significance threshold, P = .0134 and .0091, respectively second interim analysis]; RECIST version 1.1, by blinded independent central review).RESULTSMedian overall survival was longer in the pembrolizumab group than in the placebo group (14.6 v 13.0 months; hazard ratio for death, 0.79; 95% CI, 0.63 to 0.99; P = .0180). Median PFS was also longer in the pembrolizumab group than in the placebo group (2.6 v 2.3 months; hazard ratio for progression or death, 0.74; 95% CI, 0.60 to 0.92; P = .0032). ORR was greater in the pembrolizumab group (12.7% 95% CI, 9.1 to 17.0]) than in the placebo group (1.3% 95% CI, 0.2 to 4.6]; P < .0001). Treatment-related adverse events occurred in 66.9% of patients (grade 3, 12.0%; grade 4, 1.3%; grade 5, 1.0%) in the pembrolizumab group and 49.7% of patients (grade 3, 5.9%; grade 4, 0%; grade 5, 0%) in the placebo group.CONCLUSIONIn patients from Asia with previously treated advanced HCC, pembrolizumab significantly prolonged overall survival and PFS, and ORR was greater versus placebo.